The Use of Technology in Islamic Religious Education Learning to Increase Student Learning Motivation at Muhammadiyah Senior High School, Bima City - Reka Purnama; Lutfiyah; Kaharudin (Literasi: Jurnal Pendidikan Guru Indonesia, 2026)
This study aims to describe the use of technology in Islamic Religious Education (IRE) instruction and its impact on student motivation at Muhammadiyah High School in Bima City. This study employs a descriptive qualitative approach, utilizing data collection techniques such as semi-structured interviews, participant observation, and documentation. The results indicate that the use of technology such as PowerPoint, educational videos, WhatsApp groups, and interactive quizzes plays a role in creating a more engaging, communicative, and contextual learning environment. The use of technology has been shown to enhance students’ attention, participation, and understanding of IRE content, particularly when the material is linked to digital phenomena and adolescent life. However, increased learning motivation does not occur automatically. Its success is heavily influenced by the quality of instructional design, the teacher’s pedagogical ability to guide reflective discussions, and the reinforcement of Islamic values within the learning process. Identified barriers include limited internet connectivity, insufficient learning devices, and teachers’ digital literacy. This study reaffirms that technology serves as a supporting tool, while teachers remain the primary facilitators in fostering meaningful learning motivation